Perbandingan Efektivitas Buah Mangga, Jeruk, dan Naga terhadap Penurunan Kadar Low-Density Lipoprotein (Studi pada Tikus Sprague Dawley Hiperkolesterolemia) - Zaki, Ibnu; Sulistyaning, Afina Rachma; Sari, Hesti Permata; Ayu Kurnia Putri , Widya; Munawar, Farras Fauzan (Media Gizi Kesmas, 2024)
Background: Hypercholesterolemia is a condition where cholesterol levels in the blood exceed normal limits. Fruits such as Gedong Gincu mango, sweet orange, and red dragon fruit contain nutrients that can lower cholesterol levels. Objectives: The research aims to analyze the effectiveness of Gedong Gincu mango, sweet orange, and red dragon fruit in reducing LDL cholesterol levels. Methods: Using a randomized controlled pre-posttest design, the subjects involved experimental animals (rats), totaling 30, randomly divided into five groups. Group K1 received standard feed, while K2, K3, K4, K5 were given High Fat Diet (HFD) until they developed hypercholesterolemia. Subsequently, K3 received Gedong Gincu mango 3.6 mL/200 g BW, K4 sweet orange 9 mL/200 g BW, and K5 red dragon fruit 3.6 mL/200 g BW. Result: The research results indicate that group K3 had an average change in LDL levels of -38.65±3.44 mg/dL (p=0,000) , K4 (-48.36±3.80 mg/dL, p = 0,000), and K5 (-51.88±2.21 mg/dL, p = 0,000). Conclusion: The administration of Gedong Gincu mango, sweet orange, and red dragon fruit reduces LDL cholesterol. The administration of dragon fruit has a higher effectiveness in reducing LDL cholesterol by -51.88±2.21 mg/dL.